Book review: Kalpana Ram, Fertile Disorder: Spirit Possession and its Provocation of the Modern. (February 2019) - Janarthanan, Dhivya
Kalpana Ram, Fertile Disorder: Spirit Possession and its Provocation of the Modern . Honolulu: University of Hawaii Press, 2013, xiii+317 pages, US$ 57 (hardcover). ISBN: 978-0-8248-3630-6.